Tulou As A Customary Criminal Sanction in Mentawai: Convergensi of Customary and Islamic Law for Social Reconciliation - Rosman, Edi; Elfiani, Elfiani; Azizah, Hidayatul; Yufriadi, Ferdi (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2025)
This study examines the role of Tulou as a customary criminal sanction in the Mentawai Islands, particularly in cases of sexual harassment, and its relevance to Islamic criminal law. The research problem arises from the tension between the persistence of indigenous customary practices and the formal state legal system, as well as the possibility of their convergence with Islamic law in achieving justice. The central questions addressed are: How is Tulou applied as a mechanism of sanction in Mentawai society, and to what extent can its principles be aligned with Islamic criminal law? Methodologically, this study adopts a normative legal research approach combined with a socio-legal perspective, utilizing document analysis, court decisions, and in-depth interviews with customary leaders, community figures, victims’ families, and religious leaders. The findings indicate that Tulou functions as a restorative justice mechanism by prioritizing reconciliation, acknowledgment of wrongdoing, apology, and compensation, thereby restoring social harmony and protecting communal dignity. When analyzed through the lens of Islamic criminal law (fiqh jināyah), Tulou resonates with the principles of ta‘zīr and the objectives of maqāṣid al-sharī‘ah, particularly the protection of dignity (‘ird), justice (‘adl), and public welfare (maṣlaḥah). This study is novel in its exploration of Tulou as a customary sanction within a predominantly non-Muslim society through the lens of Islamic criminal law. Unlike previous works that separate customary and Islamic law, this research highlights their convergence in achieving maqāṣid al-sharī‘ah objectives such as dignity, justice, and public welfare. In doing so, the study contributes a new perspective to the discourse on restorative justice in plural legal contexts.